PENENTUAN TOTAL FENOLIK, TOTAL FLAVONOID DAN AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN BAWANG KUCAI (Allium tuberosum) - Jihan Shofwatul Islam Dalilah Aziz; Mirwa Adiprahara Anggarani (Unesa Journal of Chemistry, 2021)
The purpose of this research was to determine total phenolic, total flavonoid and antioxidant activity of chinese leeks extract. The extraction process involves a method of leveling using three different types of solvents are dichloromethane, ethyl acetate and ethanol 96%. The samples tested included analysis of total phenolic using Folin-Ciocalteau method, total flavonoid using colorimetric aluminum chloride method and antioxidant activity using DPPH method. The results showed that dichloromethane extract was not found phenolic and flavonoid compounds that are potential as antioxidants. Total phenolic content in ethyl acetate and ethanol extract were 9.5975 mg GAE/g extract and 11.8015 mg GAE/g extract. Total flavonoid content were 4,3454 mg QE/g extract and 7,7165 mg QE/g extract. The value of IC50 on ethyl acetate extract were 563,1250 ppm and and ethanol extract 312,5532 ppm, which are categorized as weak antioxidant. Keywords: chinese leeks, total phenolic, total flavonoid, antioxidant activities